Peningkatan Pengetahuan Siswa Melalui Edukasi tentang Pencegahan Covid-19 - Tri Indah Rizky; Yunita Liana; Meta Nurbaiti; Raden Surahmat; Mareta Akhriansyah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Covid-19 is an infectious disease that knows no age limit, can occur in infants, children, adolescents, adults, and the elderly. Knowledge about the Covid-19 disease is very important so as not to cause an increase in the number of Covid-19 cases. Students need to get easy-to-understand education about Covid-19 and how to prevent it and must be applied in everyday life both at school and at home. The purpose of the activity is to increase student knowledge about preventing Covid-19. The form of community service activities through education are lectures and demonstrations. The target of the activity is students at Madrasah Ibtidaiyah Mu'allimin Islamiyah Sidomukti Sekayu. The implementation time is 17-18 June 2021. The media used in the leaflet. Evaluation methods include; pretest and posttest regarding students' knowledge about Covid-19 prevention. The instrument for evaluation is a questionnaire distributed before and after educational activities. The data from the pretest and posttest evaluations of community service activities were analyzed using descriptive analysis techniques.